1996
DOI: 10.1016/s1074-5521(96)90170-2
|View full text |Cite
|
Sign up to set email alerts
|

In vitro selection of self-cleaving DNAs

Abstract: Despite the absence of 2' hydroxyls, single-stranded DNA can adopt structures that promote divalent-metal-dependent self-cleavage via an oxidative mechanism. These results suggest that an efficient DNA enzyme might be made to cleave DNA in a biological context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
178
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(185 citation statements)
references
References 25 publications
7
178
0
Order By: Relevance
“…Finally, DNA is easily synthesized with a variety of useful modifications and its biocompatibility makes DNAzyme-based sensors excellent tools for live-cell imaging of metal ions. As a result, several metal-specific DNAzymes have been isolated and converted into sensors for their respective metal ion cofactors, including Pb 2+ (35,42,43), Cu 2+ (44,45) However, in contrast to the previously reported DNAzymes with divalent metal ion selectivity, no DNAzymes have been reported to have high selectivity toward a specific monovalent metal ion. Although DNAzymes that are independent of divalent metal ions have been obtained (53)(54)(55), including those using modified nucleosides with protein-like functionalities (i.e., guanidinium and imidazole) (56)(57)(58), no DNAzyme has been found to be selective for a specific monovalent metal ion over other monovalent metal ions.…”
Section: Significancementioning
confidence: 99%
“…Finally, DNA is easily synthesized with a variety of useful modifications and its biocompatibility makes DNAzyme-based sensors excellent tools for live-cell imaging of metal ions. As a result, several metal-specific DNAzymes have been isolated and converted into sensors for their respective metal ion cofactors, including Pb 2+ (35,42,43), Cu 2+ (44,45) However, in contrast to the previously reported DNAzymes with divalent metal ion selectivity, no DNAzymes have been reported to have high selectivity toward a specific monovalent metal ion. Although DNAzymes that are independent of divalent metal ions have been obtained (53)(54)(55), including those using modified nucleosides with protein-like functionalities (i.e., guanidinium and imidazole) (56)(57)(58), no DNAzyme has been found to be selective for a specific monovalent metal ion over other monovalent metal ions.…”
Section: Significancementioning
confidence: 99%
“…For example, a number of DNA ''aptamers'' (1) can be made that function as ligands for proteins or as highly specific receptors for small organic molecules (2)(3)(4). In addition, certain single-stranded DNAs act as artificial enzymes (4)(5)(6), catalyzing such chemical reactions as phosphoester transfer (7)(8)(9)(10)(11)(12), phosphoester formation (13), porphyrin metalation (14), phosphoramidate cleavage (15), and DNA cleavage (16). Most likely, DNA can be made to perform a much broader repertoire of catalytic activities (6).…”
mentioning
confidence: 99%
“…In a previous study (16), we reported the isolation of two distinct types of deoxyribozymes (classes I and II) that undergo oxidative self-cleavage in the presence of copper ions. By using in vitro selection (17), class II self-cleaving DNAs have been further optimized for catalytic function, and the most active structure obtained from this process has been engineered to act as a ''restriction endonuclease'' for single-stranded DNA substrates.…”
mentioning
confidence: 99%
“…The latter have been shown to discriminate against Mg 2+ , while selecting for Ca 2+ [89][90][91], Cu 2+ [92][93][94], Co 2+ [95], Zn 2+ [96], Mn 2+ [94], Pb 2+ [97], Ni 2+ [98] or a small subgroup of transition metal ions [99]. By the same means extraordinarily selective DNA biosensors for various metal ions have been engineered [100,101] (see also Chapter 8).…”
Section: Expanding the Natural Metal Repertoire Of Catalytic Rnas Andmentioning
confidence: 99%